2019
DOI: 10.1017/s1352465819000584
|View full text |Cite
|
Sign up to set email alerts
|

Rumination-focused cognitive behaviour therapy for non-responsive chronic depression: an uncontrolled group study

Abstract: Background:One-third of patients with depression do not respond satisfactorily to treatment, and approximately 20% of all patients treated for depression develop a chronic depression. One approach to more effective treatment of chronic and treatment-resistant depression is to target rumination – an underlying mechanism implicated in the development and maintenance of depression.Aim:The purpose of this uncontrolled group study was to investigate the feasibility of individual rumination-focused cognitive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Third. the intervention dose was smaller than in a comparable study ( Møller et al, 2017 ). The current treatment was administered over a shorter period, with eight instead of 12 sessions at 2 h instead of 3 h per session, and an individual session was not offered before the group sessions.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Third. the intervention dose was smaller than in a comparable study ( Møller et al, 2017 ). The current treatment was administered over a shorter period, with eight instead of 12 sessions at 2 h instead of 3 h per session, and an individual session was not offered before the group sessions.…”
Section: Discussioncontrasting
confidence: 60%
“…The treatment protocol used in the study was based on the published manuals “Rumination-Focused Cognitive-Behavioral Therapy for Depression” ( Watkins, 2018 ) and “Ruminationsfokuseret Kognitiv Adfærdsterapi for Depression” ( Møller et al, 2017 ). All material was translated to Swedish and modified to fit eight 2-h group sessions with nine participants (including 15-min breaks).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is some research which highlights the efficacy of rumination-focused CBT, most studies target psychological illnesses in isolation (Hvenegaard et al, 2020; Moeller et al, 2020; Teismann et al, 2014; Watkins, 2016) and often it is only repetitive negative thinking (RNT)-focused treatments that are investigated (Monteregge et al, 2020; Spinhoven et al, 2018). For example, a meta-analysis by Spinhoven et al (2018) investigated whether RNT-focused treatments for depression have a positive effect on RNT that may in turn result in improved depressive symptoms compared with non-RNT-focused treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Health care professionals should pay attention to postoperative psychological health in esophageal cancer patients, actively address patients' discomfort, promptly identify patients' intrusive rumination, and take effective intervention measures. Research has shown that cognitive-behavioral therapy [43], mindfulness-based cognitive therapy [44], acceptance and commitment therapy [45], and other methods can effectively reduce patients' levels of intrusive rumination. Moreover, guiding patients to adopt a positive and optimistic approach to dealing with their illness can lower their levels of kinesiophobia.…”
Section: The Mediating Roles Of Intrusive Rumination and Avoidant Copingmentioning
confidence: 99%